Protecting Mice from H7 Avian Influenza Virus by Immunisation with a Recombinant Adenovirus Encoding Influenza A Virus Conserved Antigens - E. S. Sedova; L. V. Verkhovskaya; E. A. Artemova; D. N. Shcherbinin; A. A. Lysenko; I. A. Rudneva; A. V. Lyashko; S. A. Alekseeva; I. B. Esmagambetov; T. A. Timofeeva; M. M. Shmarov (Биопрепараты: Профилактика, диагностика, лечение, 2020)
Influenza is a highly contagious disease that causes annual epidemics and occasional pandemics. Birds are believed to be the source of newly emerging pandemic strains, including highly pathogenic avian influenza viruses of the subtype H7. The aim of the study: to evaluate the ability of the recombinant human adenovirus, serotype 5, which expresses genes of influenza A highly conserved antigens (ion channel M2 and nucleoprotein NP), to provide protection to laboratory mice against infection with a lethal dose of avian influenza virus, subtype H7. To achieve this goal, it was necessary to adapt influenza A virus, subtype H7 for reproduction in the lungs of mice, to characterise it, and to use it for evaluation of the protective properties of the recombinant adenovirus. Materials and methods: avian influenza virus A/Chicken/NJ/294508-12/2004 (H7N2) was adapted for reproduction in the lungs of mice by repeated passages. The adapted strain was sequenced and assessed using hemagglutination test, EID50 and LD50 for laboratory mice. BALB/c mice were immunised once with Ad5-tet-M2NP adenovirus intranasally, and 21 days after the immunisation they were infected with a lethal dose (5 LD50) of influenza virus A/Chicken/NJ/294508-12/2004 (H7N2) in order to assess the protective properties of the recombinant adenovirus. The level of viral shedding from the lungs of the infected mice was evaluated by titration of the lung homogenates in MDCK cell culture on days 3 and 6 after infection. The level of specific antibodies to H7 avian influenza virus was determined by indirect enzyme immunoassay. Results: the use of Ad5-tet-M2NP adenovirus for immunisation of the mice ensured 100% survival of the animals that had disease symptoms (weight loss) after their infection with the lethal dose (5 LD50) of H7 avian influenza virus. The study demonstrated a high post-vaccination level of humoral immune response to H7 avian influenza virus. The virus titer decreased significantly by day 6 in the lungs of mice that had been immunised with Ad5-tet-M2NP compared to the control group. Conclusion: the Ad5-tetM2NP recombinant adenovirus can be used to create a candidate pandemic influenza vaccine that would protect against avian influenza viruses, subtype H7, in particular.